The Political Economy of Agricultural Booms - Turzi, Mariano. author. aut Link
XVII, 154 p. 5 illus., 4 illus. in color.
Keywords: This book offers an in-depth analysis of the international political economy of soybean production in Brazil, Argentina and Paraguay, by identifying the dominant private and public actors and control mechanisms that have given rise to a corporate-driven, vertically integrated system of regionalized agricultural production in the Southern Cone of South America. The current agricultural boom surrounding soybean production has been aided by cutting edge technologies, including biotechnology, leading to massive organizational changes in the agricultural sector and a significant rise in the power of special interest groups and corporations. The new international model of agricultural production empowers chemical and trading multinational companies over national governments and local producers. The author identifies the different social and political conflicts in Brazil, Argentina and Paraguay; comparing and contrasting political economy structures and policymaking, regulatory and institutional environments. Mariano Turzi is Assistant Professor of Political Science and International Relations at Torcuato Di Tella University, Argentina. He has written on the international political economy of natural resources, introducing the “Soybean Republic” (Yale Journal of International Affairs) and the “Soybean OPEC” (Current History).